Inovasi Grafting Mangga Dodol (Mangifera indica L.) Berdasarkan Tipe Mata Tunas dan Panjang Entres - Boleu, Fiktor Imanuel; Buka, Oktosea; Nusa, Davidson Corneles; Samloy, Vanhurd (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The research was conducted to determine the effect of selecting the type of entres length and bud eyes in grafting dodol mango (Mangifera indica L) on the process of bud initiation, bud height, and leaf width. The experimental design used was Randomized Complete Block Design with factorial pattern. The first treatment is the type of entres length, namely 7 cm (P1), 10 cm (P2) and 13 cm (P3) while the second treatment is the type of bud eye of the entres, namely without bud eye (M1), 1 bud eye (M2) and 2 bud eyes (M3). Based on the type of bud eye, treatments P2 and P3 showed a better effect than P1 on the bud initiation process and leaf width parameters. While in the measurement of bud height, P3 treatment showed a better effect than P2 and P1. Meanwhile, in terms of the type of buds, treatments M2 and M3 had a better effect than M1 on the process of bud initiation, bud height and leaf width. The results of the analysis of variance showed that there was an interaction between the type of length and the type of bud eye on all three parameters.